Oral Lactobacillus zeae exacerbates the pathological manifestation of periodontitis in a mouse model - Chen, Yi‐Wen; Hou, Yu‐Wen; Wang, Chuang‐Wei; Cheng, Shih‐Jung; Kuo, Wei‐Ting; Lin, Chun‐Pin; Hou, Hsin‐Han (Molecular oral microbiology, 2024)
Introduction The worldwide prevalence of periodontitis is considerably high, and its pathogenic mechanisms must be investigated and understood in order to improve clinical treatment outcomes and reduce the disease prevalence and burden. The exacerbation of the host immune system induced by oral microbial dysbiosis and the subsequent tissue destruction are the hallmarks of the periodontitis. However, the oral bacteria involved in periodontitis are not fully understood. We used the Oxford Nanopore Technologies (ONT) sequencing system to analyze metagenomic information in subgingival dental plaque from periodontitis and non‐periodontitis patients. The number of Lactobacillus zeae (L. zeae) in the periodontitis patients was 17.55‐fold higher than in the non‐periodontitis patients, suggesting that L. zeae is a novel periodontitis‐associated pathogen. Although several Lactobacillus species are used in vivo as probiotics to treat periodontitis and compete with Porphyromonas gingivalis (P. gingivalis), the roles of L. zeae in periodontitis progression, and the relationship between L. zeae and P. gingivalis needs to be investigated. Methods Both L. zeae and P. gingivalis were inoculated in the ligature‐implant site of periodontitis mice. We collected mouse gingival crevicular fluid to analyze inflammatory cytokine secretion using a multiplex assay. Intact or sliced mouse maxilla tissue was used for micro‐computed tomography analysis or hematoxylin and eosin staining, immunohistochemistry, and tartrate‐resistant acid phosphatase staining to evaluate alveolar bone loss, neutrophil infiltration, and osteoclast activation, respectively. Results We observed that L. zeae competed with P. gingivalis, and it increased inflammatory cytokine secretion at the ligature‐implant site. Similar to P. gingivalis, L. zeae promoted ligature‐induced neutrophile infiltration, osteoclast activation, and alveolar bone loss. Discussion We, therefore, concluded that L. zeae accelerated the progression of periodontitis in the ligature‐induced periodontitis mouse model.